23-hydroxybetulinic acid reduces tumorigenesis, metastasis and immunosuppression in a mouse model of hepatocellular carcinoma via disruption of the MAPK signaling pathway. Issue 9 (14th September 2022) - Tian, Dazhi; Yu, Yang; Zhang, Li; Sun, Jisan; Jiang, Wentao
Abstract : Hepatocellular carcinoma (HCC) shows recurrence and lung metastasis even after treatment. 23-hydroxybetulinic acid (23-HBA), a major active constituent of Pulsatilla chinensis, exhibits potent antitumor activities. We herein investigate the biological effect of 23-HBA on metastasis and immunosuppression in a mouse model of HCC. Microarray-based gene expression profiling was employed to identify the target genes of 23-HBA in the treatment of HCC. The effect of 23-HBA on the progression of HCC was evaluated by in-vitro cell function measurements along with in-vivo xenograft implantation, lung metastasis and CD11b + Gr1 + staining experiments. The potential mechanism involving target signaling pathway was investigated by western blot analysis. Bioinformatics analysis revealed that matrix metalloproteinase 2 (MMP2) was a key target gene mediated by 23-HBA in HCC, whereas Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis demonstrated that MMP2 mainly affects the development and metastasis of HCC. 23-HBA significantly reduced cell malignant functions in vitro while delaying the HCC growth and metastasis in vivo . In addition, the number of myeloid-derived suppressor cells was shown to be reduced following administration of 23-HBA in mice. Mechanistic analysis indicated that these effects of 23-HBA during HCC were involved with the mitogen-activated protein kinase (MAPK) signaling pathway inactivation and resulted in decreased phosphorylation of both mitogen-activated protein kinases 1/2 and extracellular signal-regulated kinase 1/2. Our study reveals that 23-HBA acts as a tumor suppressor agent and suppresses HCC tumorigenesis, metastasis and immunosuppression via blockade of the MAPK signaling pathway, suggesting that 23-HBA may serve as a promising drug target to treat HCC.